Experimento para determinação da precisão e variabilidade dos métodos pegging - Silva, Jackson Henrique Braga da (2018)
In-cylinder pressure measurements have been a fundamental tool for engine research and development since the establishment of the automotive industry. Many parameters used for analysis and development in this area are based on measured pressure values in the combustion cylinder during the burning of the fuel. Relevant performance parameters such as work done, MEP and energy release profile depend on absolute and precise cylinder pressure values. Therefore, the quality of these analyses is directly related to the accuracy and precision of the values obtained for the pressure during the process under study. Currently, some of the methodologies for measuring the pressure in the cylinder during combustion use piezoelectric transducers due to several characteristics that make them suitable for the process, such as high response time, high mechanical strength, small size that facilitates the assembly in complex systems, among others. This type of transducer has characteristics, as its inherent property of providing a response signal that varies as a function of input stimulus variation, so the transducer response is a pressure differential with respect to time, which makes it necessary to use specific methods for the determination of an initial pressure dereference for the treatment of the data and obtaining the values of absolute pressure. In the literature, there are several methods indicated for the determination of this reference pressure, such as reference methods by the intake manifold, the exhaust manifold and the politropic coefficients. In this work, an analysis of the precision and accuracy of the cited methods was carried out by comparison with a reference procedure by the crankcase, assumed as reference, which is based only on actual pressure measurements, identifying the best option between theanalyzed methods and their limitations. It was concluded that the reference method by the intake manifold was the most precise and the least accurate, since the reference method by polytropic coefficients was the most accurate and the least precise.